Macronutrient intake, physical activity, serum lipids and increased body weight in primary schoolchildren in Istanbul - (:unkn) unknown (WILEY, 2005)
Background: The aim of this cross-sectional study was to record the prevalence of underweight, overweight and obesity in primary school children living in Istanbul and to examine the relationship between increased body weight and certain cardiovascular disease (CVD) risk factors. Methods: A total of 5 10 randomly selected children aged 12 and 13 years of age (257 boys, 253 girls) were examined. Information regarding anthropometrical indices, energy and macronutrient intake, physical activity, physical fitness and lipid profile were collected. Classification of children in overweight and obese subgroups was based on the cut-off points proposed by Cole et al.(1) Results: The prevalence of underweight, overweight and obesity was found to be 15.3%, 10.6% and 1.6%, respectively. Both overweight boys and girls were found to have lower physical fitness compared to their normal-weight counterparts, but no difference was observed for energy and macronutrient intake. Overweight boys were found to have higher total cholesterol (P < 0.001), low-density lipoprotein cholesterol (P < 0.01), triglycerides (P < 0.01) and total cholesterol/high-density lipoprotein cholesterol (HDL-C) ratio (P < 0.05) compared to their normal-weight counterparts, while overweight girls were found to have lower HDL-C (P < 0.05) compared to their normal-weight peers. Conclusions: Underweight and overweight coexisted in the current population. Increased body weight was accompanied by unfavorable lipid profiles and lower fitness levels. Consequently, there is an emergent need for early identification and understanding of behavioral and physiological variables related to obesity and CVD, so that appropriate interventions can be targeted to children who are at risk for adult onset of these diseases.
Keywords: adolescents; cardiovascular disease risk factors; developing country; physical activity; underreporting; NUTRITIONAL-STATUS; ENERGY-INTAKE; CHILDREN; OBESITY; OVERWEIGHT; FAT; ADOLESCENTS; CHILDHOOD; FITNESS; PLASMA